Science Teachers’ Understanding of Creative Thinking and How to Foster It as Mandated by the Australian Curriculum - McLure, F.; Won, Mihye; Treagust, David (2024)
Developing students’ creativity is an important educational goal in many countries. The Australian Curriculum Authority has mandated that all teachers teach creative thinking across all subjects and grades. However, after more than 10 years working within this mandate, how do science teachers see their role in promoting creativity in the classroom? This study reports interviews with 13 Australian science teachers, from three jurisdictions, about how they understand creativity, the activities that they use and barriers to supporting creative thinking in classrooms. The findings showed that, although teachers were able to identify many of the elements of creativity and creative thinking described in the literature, many still felt unsure of what creative thinking entails. For class activities that foster creative thinking most teachers focused on project-based or inquiry learning which require long periods of class time to complete. Less emphasis was given to the importance of developing creative thinking skills in making hypotheses by supporting construction of meaning, providing personal insights and explanations through the use of possibility thinking, mental images, analogies when teaching curriculum content. The Australian Curriculum documents themselves give guidance suggesting that creative thinking in science is mainly developed through inquiry-based activities. It is imperative that schools give more support to teachers to understand and develop creative thinking tasks, including time, resources, professional learning, and accountability systems.